Visuo-motor behavior rehearsal training (VMBR) approach in enhancing novice archer shooting accuracy performance / Muhammad Rafiudin Sa’ari and Kalam Azad Isa - Sa’ari, Muhammad Rafiudin; Isa, Kalam Azad (Universiti Teknologi MARA Cawangan Pahang, 2019)
Imagery has been shown as an effective psychological tool in enhancing sports performance. While most studies focusing on expert archers as subject, limited findings were discovered using novice athlete to measure the imagery training effect on shooting accuracy. This study aims to identify the effect of mental imagery training on novice archery athlete performance; and to compare the differences in shooting accuracy between novice and expert archers. The intervention cross-sectional research design was used in this study, which involved pre and post-test with Visuo-Motor Behavior Rehearsal Training (VMBR) as treatment intervention. Subjects were 12 archery athlete employed from Majlis Sukan Negara (Pahang) age 15.8(1.03) years old. Subjects were purposely assigned into experiment and control group base on the team their represented. Shooting accuracy data were recorded for both novice and expert groups and paired sample t-test were used to analyze the mean differences in shooting score with pearson correlation to analyse the correlation between score. As for the findings, novice archers shooting score have improved in comparing pre-test score 73.83 (9.806) and post-test score 81.83(7.80) with t(5) = 4.619, p =.0057 < .05. The novice archers also showed positive correlation in shooting test with r = .9085, p = .00, R2 = .8101. This study had concluded imagery training approach indeed has proven a beneficial training method for increasing the novice archers shooting accuracy. However, further investigation needs to be done to test the shooting accuracy on real game situation to analyse athlete performance when under competition environment.